Low-threshold potassium currents stabilize IID-sensitivity in the inferior colliculus - Karcz, Anita; Rübsamen, Rudolf; Kopp-Scheinpflug, Cornelia (Frontiers in Neural Circuits, 2012)
The inferior colliculus (IC) is a midbrain nucleus that exhibits sensitivity to differences in interaural time and intensity (ITDs and IIDs) and integrates information from the auditory brainstem to provide an unambiguous representation of sound location across the azimuth. Further upstream, in the lateral superior olive (LSO), absence of low-threshold potassium currents in Kcna1−/− mice interfered with response onset timing and restricted IID-sensitivity to the hemifield of the excitatory ear. Assuming the IID-sensitivity in the IC to be at least partly inherited from LSO neurons, the IC IID-encoding was compared between wild-type (Kcna1+/+) and Kcna1−/− mice. We asked whether the effect observed in the Kcna1−/− LSO is (1) simply propagated into the IC, (2) is enhanced and amplified or, (3) alternatively, is compensated and so no longer detectable. Our results show that general IC response properties as well as the distribution of IID-functions were comparable in Kcna1−/− and Kcna1+/+ mice. In agreement with the literature IC neurons exhibited a higher level-invariance of IID-sensitivity compared to LSO neurons. However, manipulating the timing between the inputs of the two ears caused significantly larger shifts of IID-sensitivity in Kcna1−/− mice, whereas in the wild-type IC the IID functions were stable and less sensitive to changes of the temporal relationship between the binaural inputs. We conclude that the IC not only inherits IID-sensitivity from the LSO, but that the convergence with other, non-olivary inputs in the wild-type IC acts to quality-control, consolidate, and stabilize IID representation; this necessary integration of inputs is impaired in the absence of the low-threshold potassium currents mediated by Kv1.1.